How to Motivate Engineering Education Faculty for Instructional Innovation: The Digital Leadership Effectiveness Test - Wang, Min; He, Shouxin; Li, Yanting; Lin, Mei (International Journal of Engineering Pedagogy (iJEP), 2025)
Faculty instructional innovation is the driving force behind engineering education reform and an important guarantee to promote the modernization of engineering education. With the advent of the digital era, digital leadership has become a key factor in encouraging faculty instructional innovation. Therefore, based on resource conservation theory and social cognition theory, this study explores the relationship between digital leadership, digital self-efficacy, and engineering education faculty instructional innovation and analyzes the mediating role of digital self-efficacy. Through the analysis of 316 valid samples, the results show that digital leadership and digital self-efficacy have a significant positive impact on engineering education faculty instructional innovation. Digital leadership also has a significant positive impact on digital self-efficacy, and digital self-efficacy plays a mediating role in the effect of digital leadership on engineering education faculty instructional innovation. This study reveals the impact and mechanism of digital leadership on engineering education faculty instructional innovation and provides empirical support for improving faculty instructional innovation in engineering education.